The intriguing phospholipases A2 homologues: Relevant structural features on myotoxicity and catalytic inactivity - Santos, Juliana I. Dos [UNESP] (2009)
Phospholipases A2 homologues are found in the venom of Crotalinae snakes, being their main action related to myonecrosis induction. Although many studies on these toxins had already been performed, their mechanism of action remains unclear. Here, important aspects about these toxins are reviewed, including their correct biological assembly and how essential is the natural substitution D49K for their catalytic inactivity. © 2009 Bentham Science Publishers Ltd.